Microstructural design and properties of PMNT crystal-embedded barium calcium zirconate titanate ceramics - Jaimeewong P. (2017)
© 2017 Elsevier Ltd and Techna Group S.r.l. In this study, BCZT-0.02Bi ceramics embedded with PMNT single crystals in the amount of 1, 3 and 5 wt% were prepared. The ceramics were sintered in the temperature range of 1100–1200 °C for 2 h. All the samples were characterized in terms of microstructure, and dielectric and ferroelectric properties. The microstructural characterization revealed good interfaces between PMNT single crystals and BCZT-0.02Bi grains. The addition of PMNT single crystals was found to increase the dielectric constant of the ceramics. The temperature dependences of dielectric permittivity and ferroelectric hysteresis loops also indicated an increase in relaxor behavior with increasing PMNT content. The important factors related to the relaxor behavior in this material system were discussed in detail. The BCZT-0.02Bi-xPMNT ceramic composites with exceptionally large dielectric constant with very low loss and linear P-E behavior may be used as a viable replacement for lead-based materials in electromechanical actuators and sensors and in frequency-tunable capacitors.